No outsiders : everyone different, everyone welcome preparing children for life in modern Britain - Moffat, Andrew (Routledge, 2020)
"The No Outsiders programme promotes an ethos of inclusion and intolerance, and aims to prepare children for life in modern Britain. Expanding the scheme published in the 2015 book, No Outsiders in Our Schools, this book is designed to further support educators as they make the No Outsiders ethos part of their school culture at a time when messages of fear and division are rife. Written by a practising teacher whose work to promote equality has been globally celebrated, this book provides lesson plans for use in classes from EYFS to year 6. Key features of the resource include: Plans for delivering the No Outsiders message through assemblies and classes, allowing for a flexible approach. Recommendations for picture books that can be used to support messages of diversity and inclusion. A scheme of work designed to meet the requirements of the Equalities Act (2010) and will support teachers as they prepare to implement the new Relationships Education curriculum (2020) It is the responsibility of primary schools to promote equality and diversity. This is a vital resource for all teachers and trainee teachers as they prepare children for a life where diversity is embraced and there is no fear of difference"--